2022
DOI: 10.1055/s-0041-1741505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Neoplastic Meningitis Associated with Breast Cancer

Abstract: Background Neoplastic meningitis (NM) is considered as a terminal event with poor prognosis. Its impact in clinical oncology is growing. Objective To analyze the clinical outcome of patients with carcinoma breast diagnosed with NM. Materials and Methods This study was an observational study in breast cancer patients diagnosed with NM. Patients with typical clinical symptoms and signs with either presence of cerebrospinal fluid (CSF) cytology positive for neoplastic cells or typical radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This is reflected also in the fact that all patients in the current study already had CNS symptoms. Similar experience was reported by Abraham and colleagues in breast cancer 23 where nearly all patients were symptomatic with headache (47%), vomiting (47%), diplopia (20%), and seizure (20%) being the most common symptoms. In a large experience from prospective studies in NSCLC, the symptoms of leptomeningeal disease were symptoms of altered higher mental functions (48.4%) or seizures and Headache and dizziness (32.2%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is reflected also in the fact that all patients in the current study already had CNS symptoms. Similar experience was reported by Abraham and colleagues in breast cancer 23 where nearly all patients were symptomatic with headache (47%), vomiting (47%), diplopia (20%), and seizure (20%) being the most common symptoms. In a large experience from prospective studies in NSCLC, the symptoms of leptomeningeal disease were symptoms of altered higher mental functions (48.4%) or seizures and Headache and dizziness (32.2%).…”
Section: Discussionsupporting
confidence: 82%
“…In a LMC experience reported from Kochi (State of Kerala), the commonest site leading to LMC was breast (45%) followed by lung cancer (35%). 21 Other large experiences from India (>1100 patients) by Patil and colleagues 22 and Abraham and colleagues, 23 were in lung cancer and breast cancer respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LM is a rare but very aggressive metastatic diagnosis with poor outcome. A recent study from India reported the median time to develop LM from the time of diagnosis of breast cancer was 6 months and the median overall survival (OS) was 3 months ( 3 ). This case report reported a 38-year-old woman developed LM during neo-adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%